2018
DOI: 10.1152/ajprenal.00306.2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of erythropoietin receptor activity on angiogenesis, tubular injury, and fibrosis in acute kidney injury: a “U-shaped” relationship

Abstract: The erythropoietin receptor (EpoR) is widely expressed but its renoprotective action is unexplored. To examine the role of EpoR in vivo in the kidney, we induced acute kidney injury (AKI) by ischemia-reperfusion in mice with different EpoR bioactivities in the kidney. EpoR bioactivity was reduced by knockin of wild-type human EpoR, which is hypofunctional relative to murine EpoR, and a renal tubule-specific EpoR knockout. These mice had lower EPO/EpoR activity and lower autophagy flux in renal tubules. Upon AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 97 publications
0
35
1
Order By: Relevance
“…Acikgoz' study showed that the antifibrotic effect of EPO on rats with obstructive renal fibrosis may be regulated by nuclear factor kappa B (NF-rB) signaling pathway [17]. Shi et al [18] showed that EPO can protect acute renal ischemiareperfusion injury in mice and is closely related to the activity of EPO receptor. However, the other study suggested that although EPO has protective effects on renal function and structure in renal ischemia-reperfusion injury, the extraphysiological dose required for renal protection contributes to fibrosis and chronic kidney disease [9], which inconsistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Acikgoz' study showed that the antifibrotic effect of EPO on rats with obstructive renal fibrosis may be regulated by nuclear factor kappa B (NF-rB) signaling pathway [17]. Shi et al [18] showed that EPO can protect acute renal ischemiareperfusion injury in mice and is closely related to the activity of EPO receptor. However, the other study suggested that although EPO has protective effects on renal function and structure in renal ischemia-reperfusion injury, the extraphysiological dose required for renal protection contributes to fibrosis and chronic kidney disease [9], which inconsistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The fibrotic area and fibrosis intensity were quantified with Image J program with established methods. 40,41,47…”
Section: Kidney Histology and Histopathologymentioning
confidence: 99%
“…Four-micrometer sections of paraffin-embedded kidney were subjected to immunohistochemistry following established protocols. 36,40,41,47 Total kidney lysate covering all kidney zones were prepared and subjected to SDS-PAGE as described. 40,47…”
Section: Immunohistochemistry and Immunoblottingmentioning
confidence: 99%
“…Recently, the innate repair mechanism in AKI has attracted great attention, which is highlighted by an innate repair receptor, a heterodimer of erythropoietin (EPO) receptor and β common receptor (EPOR/βcR) (Brines and Cerami 2012). EPO, a natural ligand of EPOR/βcR, is defective in tissue protection due to low a nity, but high a nity to a homodimer receptor (EPOR) 2 in erythropoiesis (Gobe et al, 2014;Wang et al, 2017;Shi et al, 2018). EPO-derived helix B surface peptide (HBSP) and cyclic HBSP (CHBP, more stable and potent than HBSP (Yang et al, 2014b)) only bind with EPOR/βcR, so remaining the tissue protective property without erythropoiesis, and have promising potential for clinical application (Brines et al, 2008;Patel et al, 2012;Wu et al, 2013;Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%